2016
DOI: 10.3389/fnbeh.2016.00081
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Echo Information Guides Flight in the Big Brown Bat

Abstract: Animals rely on sensory feedback from their environment to guide locomotion. For instance, visually guided animals use patterns of optic flow to control their velocity and to estimate their distance to objects (e.g., Srinivasan et al., 1991, 1996). In this study, we investigated how acoustic information guides locomotion of animals that use hearing as a primary sensory modality to orient and navigate in the dark, where visual information is unavailable. We studied flight and echolocation behaviors of big brown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 44 publications
6
27
0
Order By: Relevance
“…5). This observation is consistent with previous observations that bats do not adjust flight velocity to the strength of echo-acoustic flow (Kugler et al, 2016;Warnecke et al, 2016).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…5). This observation is consistent with previous observations that bats do not adjust flight velocity to the strength of echo-acoustic flow (Kugler et al, 2016;Warnecke et al, 2016).…”
Section: Resultssupporting
confidence: 93%
“…Experimental and theoretical work has provided evidence that bats respond to echo-acoustic flow (Kugler et al, 2016;Lee et al, 1992;Müller and Schnitzler, 1999;Warnecke et al, 2018aWarnecke et al, , 2016. Although explicit information about the distance of objects is provided by echolocation through the delay between call emission and echo arrival time (Simmons, 1971), echo-acoustic flow is used to adjust the lateral distance along structured surfaces (Kugler et al, 2016;Warnecke et al, 2016). This behaviour is often observed, for example, in bats following the edges of vegetation in commuting flight (Holderied et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The degree and direction of the shift depended on the sequence of pulses and echoes that were presented. This, and other recent neurophysiological (Beetz et al, 2016) and behavioral studies (Kugler et al, 2016;Warnecke et al, 2016), shows that bats are specialized for integrating the flow of echoes as they return from multiple sonar pulses.…”
Section: Neural Basis Of Echolocationsupporting
confidence: 59%
“…Previous research has shown that echolocating bats navigate densely cluttered spaces with ease, adapting their flight and echolocation signal design to optimize information extracted from complex echo soundscapes (Falk et al, 2014(Falk et al, , 2015Hiryu et al, 2010;Petrites et al, 2009;Warnecke et al, 2016;Wheeler et al, 2016). Most studies investigating the bat's behavior in complex environments have challenged the animal to maneuver around obstacles that reflect uncontrolled echo-acoustic variables, which are difficult to quantify across individual subjects and trials (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Moss et al, 2014). Recently, we attempted to address this limitation by studying the bat's echolocation and flight behavior in an experimentally controlled corridor, in which we systematically manipulated echo-acoustic information (Warnecke et al, 2016). Specifically, we quantified the echolocating bat's flight trajectory and timing of biosonar signals in response to different echo flow patterns.…”
Section: Introductionmentioning
confidence: 99%